Food‐derived hydrophilic antioxidant ergothioneine is distributed to the brain and exerts antidepressant effect in mice. Issue 6 (22nd April 2016) - Nakamichi, Noritaka; Nakayama, Keigo; Ishimoto, Takahiro; Masuo, Yusuke; Wakayama, Tomohiko; Sekiguchi, Hirotaka; Sutoh, Keita; Usumi, Koji; Iseki, Shoichi; Kato, Yukio
Abstract: Background: Clinically used antidepressants suffer from various side effects. Therefore, we searched for a safe antidepressant with minimal side effects among food ingredients that are distributed to the brain. Here, we focused on ERGO (ergothioneine), which is a hydrophilic antioxidant and contained at high levels in edible golden oyster mushrooms. ERGO is a typical substrate of carnitine/organic cation transporter OCTN1/SLC22A4, which is expressed in the brain and neuronal stem cells, although little is known about its permeation through the BBB (blood–brain barrier) or its neurological activity. Methods: To clarify the exposure of ERGO to brain and the possible antidepressant‐like effect after oral ingestion, ERGO or GOME (golden oyster mushroom extract) which contains 1.2% (w/w) ERGO was mixed with feed and provided to mice for 2 weeks, and then ERGO concentration and antidepressant‐like effect were evaluated by LC‐MS/MS and FST (forced swimming test) or TST (tail suspension test), respectively. Results: Diet containing ERGO or GOME greatly increased the ERGO concentrations in plasma and brain, and significantly decreased the immobility time in both FST and TST. The required amount of GOME ( 37 mg/day) to show the antidepressant‐like effect corresponds to at most 8 g/day in humans. In mice receiving GOME‐containing diet, doublecortin‐positive cells showed a significant increase from the basal level, suggesting promotion of neuronal differentiation. Conclusion: Thus, orally ingested ERGO is transported across the BBB into the brain, where it may promote neuronal differentiation and alleviate symptoms of depression at plausibly achieved level of daily ingestion. Abstract : This paper deals with the first demonstration of the antidepressant‐like effect of the food edible mushroom component ERGO (ergothioneine) and the possible mechanism involved, in addition to the discussion on the pharmacokinetics of ERGO. Our results indicate that the antioxidant ERGO is highly distributed to the brain across the blood–brain barrier in a transporter‐mediated manner after oral ingestion, and may exert its antidepressant‐like effect at least partially via promotion of neuronal differentiation in the hippocampal dentate gyrus.